Effect Of Climate Change Litigation and Court Decision on Corporate Stock Price - Ngwakwe, Collins, C (Acta Universitatis Danubius. Juridica, 2023)
climate litigation rulings are widely viewed as the ultimate tool to enforce climate compliance. The objective of this paper is to evaluate whether a ruling on climate litigation has an impact on corporate share price and the direction of the effect. Prior work inclination is on the concept of climate law entropy and the recent case ruling on Lufthansa’s climate litigation. The methodology is mixed with a review of relevant literature and mini-quantification of value difference using a t-test to analyse difference in mean share price before and after climate litigation ruling on Lufthansa, and finally a formulation of framework. Findings show that unlike previous ubiquitous literature findings, the share price of Lufthansa experienced a significant increase in value after the climate litigation ruling with a significant p-value of less than 0.01 (which indicates high significance level of difference in share price). The paper has practical and theoretical implications, for business law academics and for practitioners. Climate litigation may serve a dual role of enforcing climate law compliance and instilling corporate legitimacy. The paper contributes original value to corporate climate litigation literature by proposing a novel conceptual framework for understanding the diverse differential impact of climate litigation on corporate share price.